Situation Report: Yugoslavia, 22 January 1987 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Serbian Academy Defies the Party / by Slobodan Stankovic Recent Developments in Church-State Relations / by Milan Andrejevich Party Complains about Excessive Freedom of the Press / by Milan Andrejevich Generating Liberal Ideas in Slovenia / by Slobodan Stankovic Belgrade Protests: Romania "Plugging In" to Yugoslav Power / by Slobodan Stankovic